STUDY OF ADSORPTION OF THE BLUE DYE OF INDUSTRIAL WASTE WATER USING POMEGRANATE PEEL (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2019)
In this study ,the adsorption of an industrial blue dye was investigated by usingpomegranate peel in different size . The effect of the process parameters such as , contact time; adsorbate concentration pH) and (temperature ) are reported . "Nearly 2-3 hr of contact timeare found to be sufficient for the adsorption to reach equilibrium" (Abetter fixation wasobtained at acidic pH (2) and room temperature 25?C.